2016
DOI: 10.4236/jep.2016.74051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oil and Gas Activities on Acidity of Rain and Surface Water of Niger Delta, Nigeria: An Environmental and Public Health Review

Abstract: Acidic aerosols resulting from gas flaring and refinery operations in the Niger Delta are a serious environmental and public health concern. Several thousand tons of flue gas components (dust particles, SOx, CO and NOx) are released into the atmosphere by flaring billions of cubic meters of natural gas and refining and volatilizing the spilt oil. Heat waves are generated by flaring travels several meters away from flare points, destroying crops, farm lands, exotic species that are hunters delight while causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The result is that life expectancy at birth in the Niger Delta region is now 40 years as opposed to the national average of 52.9 years (CBN, 2015;Giwa et al, 2017). Several studies have also demonstrated the negative effects of gas flaring on agriculture, which is a key source of livelihood in the Niger Delta (Ologunorisa, 2001;Environmental Rights Action et al, 2005;UNDP, 2006;Gboyega et al, 2011;Nduka et al, 2016). Farmers in the Niger Delta communities regularly experience acid-like damage to their crops.…”
Section: Contextualizing the Political Economy Of Gas Flaring In Nigeriamentioning
confidence: 99%
“…The result is that life expectancy at birth in the Niger Delta region is now 40 years as opposed to the national average of 52.9 years (CBN, 2015;Giwa et al, 2017). Several studies have also demonstrated the negative effects of gas flaring on agriculture, which is a key source of livelihood in the Niger Delta (Ologunorisa, 2001;Environmental Rights Action et al, 2005;UNDP, 2006;Gboyega et al, 2011;Nduka et al, 2016). Farmers in the Niger Delta communities regularly experience acid-like damage to their crops.…”
Section: Contextualizing the Political Economy Of Gas Flaring In Nigeriamentioning
confidence: 99%
“…Exposure to ambient concentrations of CO can have resultant formation of carboxyhemoglobin together with inhaled particles, which increase blood viscosity, thereby hampering oxygen delivery to the tissues [54]. A direct effect of gaseous emission by automobiles is acidic precipitation which affects terrestrial and aquatic ecosystems with attendant public health implication as has been widely reported in Nigeria [46,47,55]. Depending on the soil in nature, acid rain affects the soil.…”
Section: Greenhouse Effect Global Warming and Acid Rainmentioning
confidence: 99%
“…NO 2 causes lung tissue inflammation at (50-100 ppm) exposure levels, bronchitis fibrosa obliterans (150-200 ppm) exposure, death (550 ppm) exposure [56]. Skin cancers and lesion, stomach ulcers, ocular congestion or corneal problems, and epithelial cell or leukocyte damage are possible health challenges associated with exposure to acid rain [55,57]. The above chronicled facts show that emission from automobile transportation can synergize change in climate (alteration between balance in incoming and outgoing radiation elements over a period of time in the atmosphere leading to differed quality of air over time) [58] and that climate change is intricately weaved to human health.…”
Section: Greenhouse Effect Global Warming and Acid Rainmentioning
confidence: 99%
“…Also, Globally, it is the most important source of power [5,6], it represents about 40% of world total energy use [6]. Several nations are excessively reliant on petroleum for their main source of electricity and transportation fuel [7].…”
Section: Introduction 11 Importance Of Crude Oil To the Nigeria Economymentioning
confidence: 99%